Optimasi Daya Generator Angin Melalui Pitch Angle Control dengan Particle Swarm Optimization dan Genetic Algortihm - Nugroho, Herminarto; Saputra, Muhammad Akram; Anwar, Muhammad Fadil (PETIR, 2023)
In optimizing the power of the wind turbine generator (WTG) due to fluctuating wind speed, the pitch angle control is used on WTG. The pitch angle has a great influence towards the rotational speed change of the WTG. The pitch angle value is in the range of 0-90 degrees. The optimal value of the pitch angle can produce the maximum power output from the wind turbine generator. Because the pitch angle value changes with wind speed, the optimization method is carried out using Particle Swarm Optimization (PSO) method and Genetic Algorithm (GA) optimization method. By using these two methods optimally, the optimal pitch angle will be obtained dependant on changes in wind speed.